A Gas‐Phase Migration Strategy to Synthesize Atomically Dispersed Mn‐N‐C Catalysts for Zn–Air Batteries. Issue 6 (22nd April 2021) - Zhou, Qingyan; Cai, Jiajun; Zhang, Zhen; Gao, Rui; Chen, Bo; Wen, Guobin; Zhao, Lei; Deng, Yaping; Dou, Haozhen; Gong, Xiaofei; Zhang, Yunlong; Hu, Yongfeng; et al.
Abstract: Mn and N codoped carbon materials are proposed as one of the most promising catalysts for the oxygen reduction reaction (ORR) but still confront a lot of challenges to replace Pt. Herein, a novel gas‐phase migration strategy is developed for the scale synthesis of atomically dispersed Mn and N codoped carbon materials (g‐SA‐Mn) as highly effective ORR catalysts. Porous zeolitic imidazolate frameworks serve as the appropriate support for the trapping and anchoring of Mn‐containing gaseous species and the synchronous high‐temperature pyrolysis process results in the generation of atomically dispersed Mn‐N x active sites. Compared to the traditional liquid phase synthesis method, this unique strategy significantly increases the Mn loading and enables homogeneous dispersion of Mn atoms to promote the exposure of Mn‐N x active sites. The developed g‐SA‐Mn‐900 catalyst exhibits excellent ORR performance in the alkaline media, including a high half‐wave potential (0.90 V vs reversible hydrogen electrode), satisfactory durability, and good catalytic selectivity. In the practical application, the Zn–air battery assembled with g‐SA‐Mn‐900 catalysts shows high power density and prominent durability during the discharge process, outperforming the commercial Pt/C benchmark. Such a gas‐phase synthetic methodology offers an appealing and instructive guide for the logical synthesis of atomically dispersed catalysts. Abstract : A novel gas‐phase migration strategy was developed for the scale synthesis of atomically dispersed manganese and nitrogen co‐doped carbon materials (g‐SA‐Mn) as highly effective catalysts for the oxygen reduction reaction (ORR). The obtained g‐SA‐Mn catalyst exhibits a remarkable catalytic performance towards ORR and zinc‐air batteries, which manifests that this catalyst possesses the potential of practical application in electrochemical devices.